Compensatory Neural Responses to Cognitive Fatigue in Young and Older Adults - Babu Henry Samuel, Immanuel; Wang, Chao; Burke, Sarah E.; Kluger, Benzi; Ding, Mingzhou (Frontiers in Neural Circuits, 2019)
Prolonged performance of a demanding cognitive task induces cognitive fatigue. We examined the behavioral and neural responses to fatigue-induced cognitive impairments in young and older adults. Particular emphasis was placed whether the brain exhibited compensatory neural activity in response to cognitive fatigue. High-density EEG was recorded from a young (n=16; 18 to 33 years of age) and an older (n=18; 60 to 87 years of age) cohort who performed a Stroop task continuously for ~2 hours with no breaks. In the young cohort, behavioral performance declined as the experiment progressed, reflecting the impairing effects of cognitive fatigue. Neurophysiologically, in addition to declining neural activity as cognitive fatigue developed, there is also evidence of region- and time-specific increase in neural activity, suggesting neural compensation. The compensatory activities followed patterns paralleling that of PASA and ELSA observed in cognitive aging and helped to moderate fatigue-induced behavioral deterioration. In the older cohort, behavioral performance did not decline as the experiment progressed, and neural activity either declined or stayed unchanged, showing no evidence of neural compensation in contrast to the young. These results suggest that young and older adults coped with cognitive fatigue differently by exhibiting differential responses as a function of time-on-task at both the behavioral level and at the neural level.